Ariyah and Rahn (A Study of the Dynamics of Human Relations) - Mhd Aidil Al Khusaini; M. Zulhilmi Hafiz; Siti Nurbaiti; Muhammad Aji Purwanto (Penerbit Hellow Pustaka, 2024)
Ariyah is a loan which allows other people to take advantage of something that is halal for free or with the aim of helping without damaging the substance of the item, and is returned after using the benefit in a condition where the substance remains undamaged. Meanwhile, pawning in Islam is called rahn. Pawning is an activity of pawning goods as collateral for a debt transaction carried out. A person who pawns an item (rahin) to a murtahin, then the item remains the property of the guarantor (rahin). As a result, a collateral recipient (murtahin) may not use or sell the collateral before obtaining permission from the collateral provider. Meanwhile, a murtahin can ask the rahin for money if it is used to maintain the rahin's property if maintenance is needed on the item. Nowadays, this pawning has become a solution to the urgent need for money which is needed by the community.